2005
DOI: 10.1097/01.ede.0000155505.04775.33
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Gas Concentrations and Personal Particulate Matter Exposures

Abstract: Particle health effects studies that include both ambient PM2.5 and gaseous concentrations as independent variables must be analyzed carefully and interpreted cautiously, since both parameters may be serving as surrogates for PM2.5 exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
74
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 192 publications
(81 citation statements)
references
References 29 publications
5
74
1
Order By: Relevance
“…A recent study comparing ambient concentrations at this site with personal exposures in Boston has shown a high longitudinal correlation (Sarnat et al 2005) between the two measurements; the study also reported that PM 2.5 concentrations were spatially homogeneous over the Boston area. This suggests that our use of ambient concentrations is reasonable and the resulting exposure error is likely to be nondifferential.…”
Section: Discussionmentioning
confidence: 74%
“…A recent study comparing ambient concentrations at this site with personal exposures in Boston has shown a high longitudinal correlation (Sarnat et al 2005) between the two measurements; the study also reported that PM 2.5 concentrations were spatially homogeneous over the Boston area. This suggests that our use of ambient concentrations is reasonable and the resulting exposure error is likely to be nondifferential.…”
Section: Discussionmentioning
confidence: 74%
“…Although the effect of PM 2.5 remained significant after adjustment of SO 2 , its effect decreased and became statistically insignificant after adjustment for NO 2 ( Table 3). Given that our study used ambient pollutant concentrations as surrogates of personal exposure, the observed health effects attributed to NO 2 might actually be a result of exposures to fine particles (Sarnat et al 2001(Sarnat et al , 2005. At present, we cannot conclude that NO 2 is a proxy of PM 2.5 or the components Fig.…”
Section: Discussionmentioning
confidence: 84%
“…This may not be true in other locations or for other population cohorts. For example, recent analyses from our Boston exposure assessment study showed that ambient O 3 was significantly associated with corresponding personal exposures (Sarnat et al, 2005). Similarly, ambient O 3 concentrations were shown to be good surrogates for exposure to O 3 for children spending considerable time outdoors during summer camp (Brauer and Brook, 1997).…”
Section: àmentioning
confidence: 88%